Role of melatonin in autism spectrum disorders in a male murine transgenic model: Study in the prefrontal cortex. Issue 3 (18th January 2022) - Borsani, Elisa; Bonomini, Francesca; Bonini, Sara Anna; Premoli, Marika; Maccarinelli, Giuseppina; Giugno, Lorena; Mastinu, Andrea; Aria, Francesca; Memo, Maurizio; Rezzani, Rita
Abstract: Autism spectrum disorders (ASDs) are a group of clinically heterogeneous neurodevelopmental disorders sharing common features related to impaired social and communication abilities in addition to stereotyped behaviors. ASD patients present encephalic morphological, physiological, and biomolecular alterations with low levels of melatonin due to alterations in its pathways. Therefore, even if ASDs have traditionally been framed as behavioral disorders, several lines of evidence are accumulating that ASDs are characterized by certain anatomical and physiological abnormalities, including oxidative stress and inflammation in peripheral biomarkers, but likewise present in human brain tissue also characterized by alterations in synaptic remodeling and neuromodulation. Melatonin has also protective and antioxidant properties, so we can therefore hypothesize that alterations in melatonin's pathways may be one of the causes of the symptomatology of autism. The aim of the present study was to analyze the beneficial effect induced by melatonin administration and its possible mechanism of action in a transgenic mouse model of autism, immediately after weaning. The male mice were daily treated per os with melatonin (10 mg/Kg/day) or vehicle for 8 weeks starting from the sixth week of life. The antioxidant modulation, the GABAergic/glutamatergic impairment, and the synaptic remodeling in the prefrontal cortex have been evaluated. Social and repetitive behaviors were also evaluated. The behavioral results showed no statistical evidences, instead the immunohistochemical results indicated the ability of melatonin to promote the activity of antioxidant system, the GABAergic/glutamatergic equilibrium, and the synaptic remodeling. The results show that melatonin may be a possible adjuvant therapeutic strategy in ASDs. Abstract : The early chronic melatonin administration modifies the expression of key molecules involved in cognitive process in a male murine transgenic model of autism spectrum disorders (ASDs). The results show that melatonin may be a possible adjuvant therapeutic strategy in ASDs and encourage new clinical trials.